2017
DOI: 10.1587/comex.2017xbl0106
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of noise current distribution in an SiC power module using near-field magnetic scanning

Abstract: This report investigates noise current distribution in the switching operation of a silicon carbide (SiC) power module for optimization of the layout and packaging design. The noise current distribution is measured via the intensity of the near-field magnetic field, and the measurement methodology visualizes the noise current distribution on a wiring plane in the power module. The effect of a direct-current-link (DC-link) snubber capacitor on suppressing the voltage overshoot and ringing oscillation is evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It is difficult to measure a high-voltage and a large-current including radio frequency (RF) noise component with high accuracy in a highlyintegrated power conversion circuit. Our previous research work focuses the current distribution in a SiC power module identified with magnetic near-field intensity for optimizing layout design [7]. The identification of EMI noise source and the clarification of noise propagation in a power conversion circuit is important to reduce the EMI noise level.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to measure a high-voltage and a large-current including radio frequency (RF) noise component with high accuracy in a highlyintegrated power conversion circuit. Our previous research work focuses the current distribution in a SiC power module identified with magnetic near-field intensity for optimizing layout design [7]. The identification of EMI noise source and the clarification of noise propagation in a power conversion circuit is important to reduce the EMI noise level.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the EMI noise source and clarification of noise propagation in a power electronics circuit is important for reducing EMI noise levels. Our previous study [8,9] evaluated the effect of an embedded DC-link snubber capacitor in the tested power module on suppressing the voltage overshoot and high-frequency noise current via the near magnetic field intensity measurement. A power electronics circuit generally operates with a constant switching frequency and phase in a periodic steady state.…”
Section: Introductionmentioning
confidence: 99%